Wettbewerb im Gesundheitswesen - Haucap, Justus; Oberender, Peter; Zerth, Jürgen (Schriften des Vereins für Socialpolitik, 2017)
»Competition in Health Care Markets« The present book contains papers presented at the last conference of the German Economic Association's working group on competition policy organized by Peter Oberender. Topics include competition in the German health care sector with a particular emphasis on hospitals, the political dividend of local government-owned hospitals and an institutional economics analysis of the self-administered system as a guarantee for innovation and competition in the German health system.